“À faire un peu de poussière”: Environmental Health and the Asbestos Strike of 1949 - van Horssen, Jessica (Labour / Le Travail, 2012)
Abstract In mid-February 1949, workers at the Jeﬀrey Mine in Asbestos, Québec, voted to strike against the American-owned Johns-Manville Company. This work stoppage precipitated a provincial industry-wide strike that lasted for almost five months. The 1949 Asbestos strike has been incorporated into Québec’s broader political historiography, and is generally regarded as a critical turning point in the history of labour and social relations in French-speaking Canada. Yet the environmental health aspects of the conflict in Asbestos remain largely unexamined. Showing how environmental health issues were a trigger for the strike and a sustained goal of the Asbestos workers seeking improvements in their conditions of work, this article demonstrates how central dust and disease were in the negotiations and arbitration hearings involving unionized workers and the company, both in 1949 and in the years that followed. It also accents the extent to which these environmental issues became health concerns that spread throughout the community. In looking at the Asbestos strike of 1949 through the lens of environmental concerns, fresh insight is gained about the nature of one of Canada’s major labour conflicts, expanding our understanding of how health issues emerging in the workplace but extending well past it can aﬀect the nature of everyday life and well being in a resource community.